APPLICATION OF GIS-TECHNOLOGIES AND REMOTE SENSING DATA FOR DETERMINING OF GEODYNAMIC RISK ZONES ON THE MAIN PIPELINES - HOTYNIAN, V.; MYCHAK, A.; TYTARENKO, O.; KOZHAN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
The methodology and main results of the of the trunk Dolyna-Volovets and Dolyna-Rososh pipeline monitoring for the prognostication of the heightened risk zones in the mountainous condition are presented. Given risk are connected with modern geodynamic.